Answer:
x = - 5, y = - 1
Explanation:
Given the 2 equations
- 5x + 3y = 22 → (1)
- 6x + 7y = 23 → (2)
Multiplying (1) by - 6 and (2) by 5 , then adding will eliminate the x- term
30x - 18y = - 132 → (3)
- 30x + 35y = 115 → (4)
Add (3) and (4) term by term to eliminate x
0 + 17y = - 17
17y = - 17 ( divide both sides by 17 )
y = - 1
Substitute y = - 1 into either of the 2 equations and solve for x
Substituting into (1)
- 5x + 3(- 1) = 22
- 5x - 3 = 22 ( add 3 to both sides )
- 5x = 25 ( divide both sides by - 5 )
x = - 5